2011
DOI: 10.3892/ol.2011.469
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and efficacy of hepatic arterial infusion chemotherapy for advanced hepatocellular carcinoma (Review)

Abstract: Abstract. The prognosis of advanced hepatocellular carcinoma (HCC) remains poor, particularly for patients with portal vein tumor thrombosis. Chemotherapy is one of the most significant treatment options for patients with advanced HCC not indicated for hepatic resection, percutaneous ablation and transcatheter arterial chemoembolization. Systemic chemotherapy does not play a central role in the treatment of HCC due to the issue of low sensitivity for chemotherapeutic agents and the difficulties in administerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…HAIC does not use embolic material, and the chemotherapeutic agent is infused into the hepatic artery via an implanted catheter, which reduces systemic side effects by firstpass effects and maximizes drug delivery to the tumor. Although this is considered an experimental treatment modality and is not recommended for treatment of HCC in Western countries, a large amount of clinical data on HAIC have been accumulated in Eastern countries [67][68][69][70][71][72] . A small retrospective study showed survival benefits of HAIC using low doses of cisplatin and 5-fluorouracil compared with systemic cytotoxic chemotherapy or supportive care (median survival, 6, 4, and 2 mo, respectively; P = 0.003) in cases of advanced HCC with portal vein tumor thrombosis [73] .…”
Section: Medical Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…HAIC does not use embolic material, and the chemotherapeutic agent is infused into the hepatic artery via an implanted catheter, which reduces systemic side effects by firstpass effects and maximizes drug delivery to the tumor. Although this is considered an experimental treatment modality and is not recommended for treatment of HCC in Western countries, a large amount of clinical data on HAIC have been accumulated in Eastern countries [67][68][69][70][71][72] . A small retrospective study showed survival benefits of HAIC using low doses of cisplatin and 5-fluorouracil compared with systemic cytotoxic chemotherapy or supportive care (median survival, 6, 4, and 2 mo, respectively; P = 0.003) in cases of advanced HCC with portal vein tumor thrombosis [73] .…”
Section: Medical Therapiesmentioning
confidence: 99%
“…Hepatic arterial infusion chemotherapy (HAIC) has been used for treatment of advanced HCC with portal vein tumor thrombosis in Asian countries [67][68][69][70][71][72] . Traditionally, the presence of tumor thrombus is assumed to aggravate ischemic injuries after TACE, so alternative modalities were sought.…”
Section: Medical Therapiesmentioning
confidence: 99%
“…Moreover, the commonly used chemical agents usually have unexpected side-effects, such as hair loss, nausea, vomiting, and diarrhea (31). Additionally, after resection or transarterial chemoembolization, the impaired physiological function of the liver and gallbladder leads to further severe side-effects and systemic toxicity (32).…”
Section: Discussionmentioning
confidence: 99%
“…A number of prospective trials and retrospective series have reported the results of HAI in Asian patients with hepatocellular carcinoma 8,9 . The efficacy and tolerance of HAI in Asian HCC patients has also been reviewed recently [10][11][12][13]29 . Despite the fact that different cytotoxic agents have been used across the spectrum of different primary tumors, 5-fluoro-2'-deoxyuridine (floxuridine) has been traditionally regarded as an optimal agent for HAI.…”
Section: Discussionmentioning
confidence: 99%
“…While chemoembolization, another liver-directed procedure targeting the vasculature, is a standard method in the management of patients with inoperable HCC based on the results of prospective trials indicating survival benefit 7 , the utilization of HAI in this setting is less frequent. Numerous studies on HAI in HCC have been reported from East Asia, especially from Japan [8][9][10][11][12][13][14][15][16][17][18][19][20] , but the experience with this approach in the Caucasian population of Western countries is very limited 21,22 . The use of HAI is currently not recommended in therapeutic guidelines, but this approach has been used in the past.…”
Section: Introductionmentioning
confidence: 99%